Gempur Trivia Johor: Aplikasi Interaktif Warisan Budaya Negeri Johor bagi pelajar Tahun 5 dan 6 - Kamis, Mohamad Najmi; Ridzuan, Muhammad Syahmi; Sa’audi, Muhammad Nazirul Shah; Mohamed, Juliana; Mariam Abdul Hamid (Multidisciplinary Applied Research and Innovation, 2025)
This project aims to create an interactive quiz application called Gempur Trivia Johor suited for year 5 and 6 students in primary school in the field of history. The application is meant to be interactive and enjoyable for the student to be more engaged with the application. Student satisfaction and engagement are our side goals to achieve since the application is for the younger generation. Our main problem to be addressed is the lack of engagement and interactive learning methods for history topics at the educational level. The approach that is used in the history class mostly is reading and hearing. With interactive application, students would be more interested and would increase their understanding of the subject. The ADDIE (Analysis, Design, Development, Implementation, Evaluation) methodology was used in this project and the user’s interface was designed using the Figma website, while the application was developed using Flutter, an advanced software for application development. The main result of the project is the creation of an application that is both user-friendly and interactive to improve student's understanding and interest in the history of Johor. Therefore, we used a combination of various audios, images and buttons were used more frequently to enhance student understanding and interest in this application.